THE EFFECT OF BURNOUT AND PHYSICAL WORK ENVIRONMENT ON EMPLOYE PERFORMANCE-MEDIATED WORK ENGAGEMENT IN BADAN DIKLAT DIY - Nasrip, Muhamad; Pono, Nur Fajar; Maryam, Baiq Siti (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2025)
The purpose: This study aims to examine the effect of burnout and physical work environment on employee performance-mediated work engagement. Methodology: This study uses a quantitative design with a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. Data were collected through questionnaires from 66 respondents who work at the DIY Education and Training Agency. Results & Conclutions: The results of the analysis show that Burnout on Employee Performance has a significant and positive effect, Burnout does not have a positive effect on Work Engagement. Physical Work Environment on Employee Performance has a significant and positive effect. Physical Work Environment has a significant and positive effect on Work Engagement. Work Engagement on Employee Performance has a significant and positive influence on Work Engagement. burnout does not have a significant influence through work engagement on employee performance. In contrast, physical work environment was shown to significantly and positively influence employee performance through work engagement. This finding suggests that a quality physical work environment can improve work engagement and performance. Implications: This study provides important implications for management who need to focus on improving the physical work environment to encourage employee engagement and improve performance. On the other hand, the results of research on burnout suggest that factors other than work engagement should be taken into account in reducing the negative impact of burnout on employees. This research shows the importance of more comprehensive interventions in addressing burnout in the workplace